2017
DOI: 10.1039/c7tb01794d
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial hydroxyapatite–gelatin–silica composite pastes with tunable setting properties

Abstract: Bone grafting is one of the commonest surgical procedures, yet all bone substitutes developed so far suffer from specific weaknesses and the search for a bone graft material with ideal physical and biological properties is still ongoing. Calcium phosphate pastes are the most frequently used synthetic bone grafts, yet they (a) often take an impractically long time to set, (b) release the drug content too fast, and (c) do not form pores large enough to accommodate host cells and foster osseointegration. To make … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 70 publications
(66 reference statements)
0
13
0
Order By: Relevance
“…However, the mild antibacterial activity of CP nanoparticles, especially pronounced against Gram-negative strains, has not been a prime field of interest until recently. Our recent studies demonstrated that the microstructure of CP nanoparticles could be tuned to elicit a finite antibacterial response even in the absence of the delivered antibiotics . The action of antibiotics with little specificity toward specific bacterial strains can also be augmented when they are being delivered by CP nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mild antibacterial activity of CP nanoparticles, especially pronounced against Gram-negative strains, has not been a prime field of interest until recently. Our recent studies demonstrated that the microstructure of CP nanoparticles could be tuned to elicit a finite antibacterial response even in the absence of the delivered antibiotics . The action of antibiotics with little specificity toward specific bacterial strains can also be augmented when they are being delivered by CP nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent studies demonstrated that the microstructure of CP nanoparticles could be tuned to elicit a finite antibacterial response even in the absence of the delivered antibiotics. 21 The action of antibiotics with little specificity toward specific bacterial strains can also be augmented when they are being delivered by CP nanoparticles. Simultaneously, CP nanoparticles elicit a positive effect on fibroblastic, osteoblastic, and osteoclastic cells in vitro, both at the phenotypic and genotypic levels.…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable literature on the employment of particles in the formation of ultrastable foams. The addition of a surfactant that is able to adsorb on the particle surface, thus turning an initially hydrophilic to a partially hydrophobic particle gives rise to a very effective foam/emulsion stabilizer. HAp nanoparticles are characterized by a negative ζ potential in a rather wide pH range, , while the surfactant used, CTABr, bears a positively charged head. It is foreseeable that CTABr interacts electrostatically with the HAp nanoparticles’ surface making them partially hydrophobic and, as a result, able to absorb at the liquid–gas interface.…”
Section: Resultsmentioning
confidence: 99%
“…In a work by Uskoković et al from 2017 [ 69 ], a HAp-forming CPC was supplemented with silica and gelatin, which endowed the cement with thermosetting properties. The volume of the cement that would take around 45 min to set at room temperature would thus set in a matter of minutes at physiological 37 °C.…”
Section: Matrix Additivementioning
confidence: 99%